Poly (3-hydroxybutyrate) production from glycerol by marine microorganisms - Phol-in, Sathita; Kamkalong, Donlaya; Jaturapiree, Adisak; Jaturapiree, Phimchanok (Asia-Pacific Journal of Science and Technology, 2017)
Poly(3-hydroxybutyrate) (PHB)-producing bacteria generally store the PHB material as a response to nutrients imbalance i.e., the limiting of nitrogen, sulfur, phosphorus or oxygen, with an excessive carbon source. PHB production cost is relatively high due to the raw material cost. Therefore, using glycerol, a by-product from biodiesel production plant, is an economical way to solve this problem. The purpose of this study was to use glycerol as carbon source to produce PHB by marine microorganisms (M26, M27, S3, S6, and S16) that were screened and isolated from marine sediment at Samut Sakhon and Samut Prakan province, Thailand. The capability of these strains to synthesize PHB from glycerol concentration ranging from 0.0% to 6.0% (v/v) was studied. Strain M27 shows the maximum PHB content (15.87%) at 6% (v/v) glycerol concentration after 36 h shaking at 120 rpm at 37 °C. The extracted polymers were identified as PHB using 1H NMR and FTIR analysis. The results from this study can be further investigated to reduce cost of PHB production.